(untitled) (Islamic Sciences Journal, 2024)
ABSTRACT Researching the texts of the Prophet’s Sunnah, and knowing what they contain of people’s guidance and righteousness in the affairs of this world and the hereafter, requires meditating on those texts, learning about them, and knowing the rulings in them, including what relates to issues of belief, including the divine attributes. Therefore, I decided to contribute in this field by highlighting the texts in which the sensory reference that relates to the divine attributes is mentioned, through this brief research entitled “The sensory reference and the doctrinal implications resulting from it in denial and affirmation.” The research indicated highlighting the texts of the hadiths that include the sensory reference and also explaining the close connection between Issues of belief and the Prophet’s hadith, and explaining the effects of denying and proving the reference.